Patterns of Fluoride Intake from Birth to 36 Months - Steven M. Levy, DDS, MPH; John J. Warren, DDS, MS; Charles S. Davis, PhD; H. Lester Kirchner, PhD; M (Blackwell Synergy, 2001)
Dental fluorosis prevalence has increased in the United States, Canada, and other nations due to the widespread availability of fluoride in many forms, with fluoride ingestion during the first three years of life appearing most critical in fluorosis etiology. With few contemporary studies of fluoride ingestion in this age group, the purpose of this paper is to describe patterns of estimated fluoride ingestion from birth to 36 months of age from water, dentifrice, and dietary fluoride supplements and combined.